DOI: 10.3990/1.9789036528405
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic sitting

Abstract: Individuals who cannot functionally reposition themselves adopt a passive body posture and suffer from physical discomfort in long-term sitting. To regulate body load and to prevent sitting related mobility problems, proper postural control is important. The inability to reposition underlines the importance for seating interventions that control body posture from automatic chair adjustments. We developed an adjustable simulator chair that allows the alignment of the trunk, pelvis and thighs to be controlled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…However, given his lack of previous pressure ulcers, it calls into question whether the lack of response puts him at additional risk. Subject 4 is more consistent with the able-bodied non-responders seen in the study by van Geffen [11], as her blood flow was significantly higher than other participants in the upright seated position. Previous research has suggested that additional individual factors should be addressed when studying blood flow.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, given his lack of previous pressure ulcers, it calls into question whether the lack of response puts him at additional risk. Subject 4 is more consistent with the able-bodied non-responders seen in the study by van Geffen [11], as her blood flow was significantly higher than other participants in the upright seated position. Previous research has suggested that additional individual factors should be addressed when studying blood flow.…”
Section: Discussionsupporting
confidence: 76%
“…This is not surprising, as previous literature has addressed the individual nature of blood flow response [15,22,23]. Bader first suggested the idea of a "non-responder" in his 1990 paper.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations